HUBUNGAN RADIO LINE OF SIGHT ANTAR MOBIL TELEPHON EXCHANGE DAN RADIO BASE STATION - Agus Sugiharto (JURNAL TEKNOLOGI INDUSTRI, 2018)
In the development of the telecommunications world which is growing rapidly at this time, one of the technologies that is quite widely used is the use of microwaves as transmission media. The tools for transmitting microwaves are microwave links or Radiolink, among the many uses, one of which is the link between MTX / MSC / EMX and RBS / BBC / BTS. If a subscriber makes a call, the signal will automatically go through RBS first then it will be transmitted to MTX, then the call will be identified. From MTX then the signal is transmitted back to all RBS in a traffic area where the subcriber is being addressed, and this connection is full duplex. So the signals from the subscriber will be received by the inter RX in RBS which then goes into 2 MB / S digital multiplexing with a capacity of 30 channels, then from this multiplexer the signal will be modulated digitally (most of the current digital R / L is used ) in Radio Link to be transmitted to MTX. Link Radio users cannot be avoided from interference, because the air as a medium is very free. But this of course can be minimized by several calculations, such as antenna gain, net path loss and others